Display of national self-identity of visitors Tarasova hill during the period of Central Rada (1917–1918) - Bryzytska, Svitlana (Вісник Черкаського університету. Серія: Історичні науки, 2018)
Abstract. Introduction. In 2016 the 25th anniversary of Ukrainian state independence was celebrated. In the history of modern Ukraine in the time dimension, it is a long-time state creation. However, the loss of Ukraine territories in 2014 and the outbreak of hostilities on its territory brings us back again to the analysis process of the Ukrainian statehood. Therefore there is now a great need in research and rethinking this process through reminders about Ukrainian revolution events of 1917–1921. This year we celebrating 100-th anniversary of revolution 1917-1921. In particular it is important to pay attention to Central Rada (1917–1918) which was found in March 1917, since the main focus in the complex process of the Ukrainian state creation, she chose national-territorial autonomy of Ukraine. Purpose. The purpose of publishing - to show with the help of the examples (handwritten expressions) in the book of impressions during 1917-1921 years made by visitors of Taras Shevchenko’s grave, expression of their national identity and attitude to the political situation in Ukraine during the Central Rada (1917-1918). Because Taras Shevchenko for Ukrainians is not just a poet, but spiritual father of Ukrainian nation. Results. In period of Central Rada visitors-ukrainians who came at Tarasova Mountain in Kaniv where Taras Shevchenko was buried, show high level of national self-awareness. This proves their knowledge and use of native Ukrainian language, which at the time of Russian empire suffered harassment. Also confirms a massive use in the books of impressions (in signatures) ethnonym «Ukrainians» which is at that time not widely used. Ukrainians also call themselves «children», of Shevchenko and Ukraine, or refer to themselves according to the place of birth (using regional identytets) – «Poltavers» (Poltava population), «Cherkasers» and so on. They write about positive cultural and socio-political changes, supporting Universals from Central Rada while they are in agreement with the government in their desire for better future for their country and «brothers»-ukrainians. This all demonstrates the manifestation from compilers-ukrainians their national identity. Originality. Based on valuable sources - handwritten notes from Tarasova grave visitors the criteria by which during Central Rada held an emergence of Ukrainian national identity is clarified. An emergence, that led to the formation of the Ukrainian nation in the future. Conclusion. Central Rada with its policy activates consolidation process between Ukrainians among different social classes in political community, contributed to the definition and understanding of their national identity and generally contributed to increased level of consciousness development processes. Figure of Shevchenko thus took an important role as a fighter for social and national rights of Ukrainians.